Epidemiology of road traffic accidents in adults. A systematic review - Krzysztof Goniewicz; Mariusz Goniewicz; Witold Pawłowski; Dorota Lasota (Kazimierz Wielki University, 2017)
Road accidents are a serious problem of the modern world. They are one of the main causes of injuries and are the third most numerous cause of death. Every year, about one million people, adults and children, die on the roads and several millions are injured. Mortality rate due to injuries from road accidents amounts to 2,2% of all deaths in the world. The research presents a mechanism of traffic accidents, pathophysiology of injury, partition of car accidents and characterized the insults of victims in various types of automobile accidents. Injuries resulting from road accidents have numerous substantial consequences as they are related with releasing large amounts of kinetic energy which must be absorbed. Kinetic energy absorbing is the basic mechanism of injury arising during road accidents. In apprising an automobile accident should take into consideration the type of the car accident and the extent of damage to the vehicle People participating in road accidents of high energy are especially endangered with substantial injuries. There is a close relationship between the rate of vehicle damages and seriousness of casualties' injuries.